Draft genome sequence of a halotolerant plant growth-promoting bacterium Pseudarthrobacter oxydans NCCP-2145 isolated from rhizospheric soil of mangrove plant Avicennia marina - Rabia Bushra; Bushra Uzair; Ahmad Ali; Sadia Manzoor; Saira Abbas; Iftikhar Ahmed (Electronic Journal of Biotechnology, 2023)
Background: Limited knowledge exists regarding the diversity of mangrove plant-associated Pseudarthrobacter species. This study presents the first draft genome and phylogenetic analysis of a Pseudarthrobacter oxydans NCCP-2145, isolated from the rhizospheric soil of Aviciana marina, a native mangrove plant found in Miani Hor, Lasbela-Baluchistan, Pakistan. Results: The genome of P. oxydans NCCP-2145 comprises 4,495,869 base pairs, with a G+C content of 65.9% and 4,207 coding sequences. Genome annotation revealed the presence of multiple biosynthesis pathways. The analysis also identified genes responsible for plant growth-promoting traits, such as the synthesis of indole acetic acid, nitrogen fixation, and phosphorus solubilization. Experimental evaluations confirmed strain NCCP-2145 positive reactions for phosphorus solubilization, indole-3-acetic acid production, and ammonia production. Furthermore, strain NCCP-2145 exhibited tolerance to heavy metals (nickel, copper, and cadmium) and salinity levels up to 10% NaCl. Antibiotic susceptibility testing indicated resistance only to ceftazidime and the combination of amoxicillin/clavulanic acid. For phylogenomic analysis, strain NCCP-2145 was analyzed and compared to the closely related validly published type species P. oxydans DSM 20119T, revealing a similarity score of 98.64% based on 16S rRNA gene sequences and 89.1% based on DNA-DNA hybridization, confirming its classification as a member of species, P. oxydans. Conclusions: This study significantly contributes to our understanding of the genomic characteristics, functional capabilities, and potential plant growth-promoting attributes of P. oxydans NCCP-2145. Future research should focus on unraveling the precise mechanisms underlying its plant growth-promoting abilities and exploring practical applications in sustainable agriculture and environmental restoration.How to cite: Bushra R, Uzair B, Ali A, et al. Draft genome sequence of a halotolerant plant growth-promoting bacterium Pseudarthrobacter oxydans NCCP-2145 isolated from rhizospheric soil of mangrove plant Avicennia marina. Electron J Biotechnol 2023;66. https://doi.org/10.1016/j.ejbt.2023.08.003.